2020
DOI: 10.1111/jgs.16472
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and Older Adults: What We Know

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel virus that causes COVID-19 infection, has recently emerged and caused a deadly pandemic. Studies have shown that this virus causes worse outcomes and a higher mortality rate in older adults and those with comorbidities such as hypertension, cardiovascular disease, diabetes, chronic respiratory disease, and chronic kidney disease (CKD). A significant percentage of older American adults have these diseases, putting them at a higher risk of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
710
1
58

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 858 publications
(852 citation statements)
references
References 26 publications
19
710
1
58
Order By: Relevance
“…The immunomodulatory therapy was administered shortly after the contagion. In addition to the advance age, all moderately ill patients suffered with comorbidities, which are both risk factors associated with severity and fatal outcome in the course of COVID-19 [30,31]. Therefore, we suggest that the stabilization of the IL-6 levels over low values was due to the treatment with itolizumab.…”
Section: Discussionmentioning
confidence: 90%
“…The immunomodulatory therapy was administered shortly after the contagion. In addition to the advance age, all moderately ill patients suffered with comorbidities, which are both risk factors associated with severity and fatal outcome in the course of COVID-19 [30,31]. Therefore, we suggest that the stabilization of the IL-6 levels over low values was due to the treatment with itolizumab.…”
Section: Discussionmentioning
confidence: 90%
“…Angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers are commonly used in many adults with hypertension, diabetes, and chronic kidney disease [26]. Studies have shown that these drugs up-regulate ACE-2 receptors, which are the receptors that SARS-CoV-2 virus uses to enter host cells, which may be one of the reasons why older people with comorbidities are susceptible to infection and deterioration [27]. In addition, COVID-19 damage to the lungs can aggravate some comorbidities, such as chronic obstructive pulmonary disease.…”
Section: Covid-19 Patients With Comorbidities Were Also Likely To Shomentioning
confidence: 99%
“…Public health data from the European populations studied here was searched regarding the most common COVID-19 comorbidities reported. Aging has been broadly identified as the main one [13,20,21], followed by cardiovascular disease (CVD), diabetes, chronic obstructive pulmonary disease (COPD) and cancer history [13,15]. Liver dysfunction, smoking status, chronic kidney diseases and immunodeficiency have also been reported [14][15][16].…”
Section: Mortality Rate Frequency Calculationmentioning
confidence: 99%